IoT and smartphone app for elderly pill management - Souza Junior, Sidnei de; Panisson, Alison R.; Ourique, Fabrício de O.; Lau, Jim; Morales, Analúcia Schiaffino (Anais Estendidos do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2023: Anais Estendidos do XIII Simpósio Brasileiro de Engenharia de Sistemas ComputacionaisDO - 10.5753/sbesc_estendido.2023.235372, 2023)
Technological advancements have greatly improved the quality of life and increased longevity. Meanwhile, the increase in the elderly population for the next years generates some concerns about the quality of life and independence of these people; A prototype for a pill monitoring system has been proposed as part of this project, which aims to contribute to this progress by developing and implementing an Internet of Things (IoT) device for pill management. The prototype allows users to input medication information, set alarms, and monitor doses. The user interface was designed to focus on intuitive and accessible interaction, considering users with low levels of mobile technology proficiency. Additionally, the application generates graphs of patient medication usage to assist healthcare professionals. To control and monitor the medication compartments, the prototype was implemented using the ESP32 microcontroller and Bluetooth or Wi-Fi communication. Regardless of the preliminary stages of development, the functional prototype has great potential to become a valuable tool for the elderly.